Triceps-off trans-fascial sleeve approach, functional outcomes and surgical technique in Distal Humerus fractures - Nkomo, Woyisile (Division of General Surgery, 2023)
Purpose: We aimed to assess functional and clinical outcomes of patients who underwent open reduction and internal fixation of distal intra-articular fractures of the humerus through a previously undescribed approach through the triceps tendon called the Triceps-Off, Transfascial Sleeve (TOFS) approach. Method: We conducted an Ambispective cohort study of 10 patients who underwent open reduction and internal fixation of the distal humerus through the TOFS approach at a tertiary hospital between March 2016 and January 2019. Patients were identified from the prospectively kept surgical database. All had AO type C fractures of the distal humerus. The mean age was 36.7 ± 14.9 years (range 19 to 68). The assessment consisted of a review of their hospital records, range of motion, triceps strength, ultrasound evaluation of triceps tendon integrity, X-rays for union rates and adequacy of reduction, and DASH scores. Results: The mean time of follow up was 10.8 ± 4.7 months (range 6 to 19). The mean arc of motion was 114.7 ± 25.1 degrees (range 80 to 150 degrees). There was a decrease in mean triceps muscle strength compared to the uninjured side; 66% at 45 degrees of flexion, 70% at 90 degrees and 86% at 120 degrees of elbow flexion. The mean DASH score was 15.7 ± 8.9 indicating mild residual impairment (range 5 to 31). The DASH score had a strong correlation (r = 0.71; p<0.05) with the follow-up period. All tendons were intact on ultrasound evaluation. One patient had deep surgical site infection, treated with surgical debridement, antibiotics and plate removal with resolution of sepsis and healing. All fractures united by 6 months. Conclusion: TOFS is a successful surgical approach for reduction and fixation of AO Type C intra-articular distal humerus fractures, with excellent tendon healing rates. It is however, associated with mild residual functional impairment and residual triceps weakness.